2015
DOI: 10.1503/cjs.005215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding Braun jejunojejunostomy to standard Whipple procedure on reduction of afferent loop syndrome — a randomized clinical trial

Abstract: Background: Whipple surgery (pancreaticodeudenectomy) has a high complication rate. We aimed to evaluate whether adding Braun jejunojejunostomy (side-to-side anastomosis of afferent and efferent loops distal to the gastrojejunostomy site) to a standard Whipple procedure would reduce postoperative complications. Methods:We conducted a randomized clinical trial comparing patients who underwent standard Whipple surgery (standard group) and patients who underwent standard Whipple surgery with Braun jejunojejunosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Stagnation of the flow of digestive juices in the jejunal loop can easily lead to reflux of digestive juices into the IHBD via anastomosis [ 18 ]. Shortening the jejunal loop to the minimum length necessary and adding the Braun's anastomosis may reduce pressure in the jejunal loop and prevent reflux of digestive fluids into the IHBD [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stagnation of the flow of digestive juices in the jejunal loop can easily lead to reflux of digestive juices into the IHBD via anastomosis [ 18 ]. Shortening the jejunal loop to the minimum length necessary and adding the Braun's anastomosis may reduce pressure in the jejunal loop and prevent reflux of digestive fluids into the IHBD [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…1. The search identified 1215 studies, of which 24 RCTs met the inclusion criteria [2][3][4][5][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] . A total of 2647 patients were randomized and 2526 included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ages, gender mix and BMI were generally comparable between direct comparisons, although the single study comparing PR, retrocolic, Billroth II against PR, antecolic Billroth II had a male-predominant cohort (more than 70 per cent). Most studies were conducted in Asia (16 of 24; 67 per cent) 5,35,36,[38][39][40][41][42][43][44][45][46]48,50,51,53 , 10 of which were in Japan 5,35,36,39,42,44,46,48,50,51 . Study characteristics are summarized in Table S1.…”
Section: Transitivity Analysismentioning
confidence: 99%
“…Braun anastomosis is one of these two strategies; it reduces the pressure in the biliopancreatic limb to avoid the afferent loop syndrome. The result of a randomized clinical trial showed that Braun anastomosis might decrease the pressure in the biliopancreatic limb after standard Whipple’s operation [19]. Separating anastomoses is the other strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Double Roux-en-Y reconstruction was proposed to isolate pancreaticoenteric, choledochoenteric, or gastroenteric anastomosis [21]. However, all these modified structures rendered no significant protection against pancreaticoenteric leakage [1921].…”
Section: Discussionmentioning
confidence: 99%